When Academics Become Parents: An Overview of Family Leave Policies at Canadian Universities - Prentice, Susan; Pankratz, Curtis J. (Canadian Journal of Higher Education, 2003)
When academic faculty become parents, how do their employers respond? This paper addresses that question through a review of family leave policies current in Canadian universities as of March 21, 2000. An analysis of pregnancy, parental, adoption, and partner ('paternity') leave policies reveals that most Canadian university policies produce income loss and disruption and are discriminatory, characterized by gender regu- lation and familialism. We assess some normative criteria for improved family leave provisions, and propose that improving faculty family leave policies would benefit all academics. In particular, improved family leave has the potential to eliminate one dimension of systemic discrimi- nation that creates "chilly climates" for female faculty. We predict that family leave issues are likely to emerge as significant concerns on Canadian campuses.